'And the Light in his Eyes Grew Dark': The Representation of Anger in an Egyptian Popular Epic. Issue 2 (October 2019) - Blatherwick, Helen
Abstract : Sīrat Sayf ibn Dhī Yazan is a late-medieval Egyptian popular epic that tells the story of the foundation of Egypt and conquest of the world by its hero, the Yemeni king Sayf. It is one of a group of narratives known as the siyar shaʿbiyya, Arabic popular epics or romances. As a genre, their core concerns are issues of identity, the collective anxieties of the social unit, and that unit's struggle to maintain its integrity. Sīrat Sayf explores these issues in large part through the thematic use of gender, according to which the male, patriarchal forces of order are in tension with the female forces of chaos in an unstable and perpetually shifting balance that must be kept in equilibrium. In this context, open displays of strong emotions by its main protagonists can take on a particularly threatening aspect in the text. This article investigates the representation of anger in Sīrat Sayf, focusing first on the extent to which it can be described as gendered, and the significance of this for an understanding of both how male and female anger are conceptualised in the text and their respective roles in its textual dynamics. It then explores the part played by anger in an episode in which King Sayf offers the choice of conversion to Islam or death to a defeated enemy. In this small but key extract, the normally formulaic 'conversion narrative' becomes a highly emotionally charged encounter, during which characters are driven by anger to break with narrative conventions and behave in unexpected ways. This 'emotional manipulation' of literary conventions, which is achieved partly through the manipulation of gendered emotional codes, is one of the ways in which the narrative is able to give voice to the tensions surrounding issues of self and other, and communal identity, but also has implications for our understanding of the social codes depicted in the text.